The FNS-based analysis of precursors and cross-correlations in EEG signal related to an imaginary motor task. (February 2021) - Broniec, A.
Abstract: Flicker noise spectroscopy (FNS) is a time series analysis method to extract information contained in complex nonlinear systems using parameters characterizing the chaotic component of signal in different frequency ranges. In the paper, FNS (precursor function and cross-correlations) is used to study electroencephalography (EEG) signal related to the hand movement imagination. Our analysis of the precursor function calculated for different electrodes reveals a distinct peak just before the imagination which allows for detection of the motor task and distinction of the hand being a subject of the imagination. The EEG rhythms in subsequent stages of the task are determined based on cross-correlation maps which are furthermore used to describe directions of flows between different parts of the sensorimotor cortex. Highlights: FNS precursor function and cross-correlations is used to study the hand MI. Nine volunteers participated in the experiment of right and left MI. The precursor function can detect the changes of the brain state related to the task. The cross-correlation function reveals changes in the EEG rhythms during the task. The cross-correlations determine the direction of the signal flow between electrodes.